Perspectives from the Field - Kristen A. Sullivan PhD, MSW, MA; Miriam B. Berger MPH; Evelyn Byrd Quinlivan MD; Heather E. Parnell MSW; Lynne A. Sampson PhD, MPH; Jacquelyn M. Clymore MS; Aimee M. Wilkin MD, MPH (Journal of the International Association of Providers of AIDS Care, 2016)
Background: HIV testing and linkage to care are critical first steps along the care continuum. Targeted efforts are needed in the South to achieve the goals of the National HIV/AIDS Strategy, and qualitative examination of testing and linkage to care from the perspective of professionals in the field can provide nuanced insight into the strengths and limitations of a care system to inform improvement efforts. These issues are explored in North Carolina (NC), with potential applicability to other Southern states. Methods: Twenty-one interviews were conducted with professionals in the HIV prevention and care systems in NC. Interviews were analyzed for emergent themes. Results: Individuals’ access barriers, aspects of clinics and clinical care, challenges for community-based organizations, stigma, and the role of the NC Department of Health and Human Services were identified as themes affecting testing and linkage. Discussion: These findings can inform efforts to address HIV testing and linkage to care in NC. This approach may provide beneficial insight for other systems of care.